Coinfection of Two Mycoviruses Confers Hypovirulence and Reduces the Production of Mycotoxin Alternariol in Alternaria alternata f. sp. mali - Li, Bo; Cao, Yuhan; Ji, Zixuan; Zhang, Jingyi; Meng, Xianglong; Dai, Pengbo; Hu, Tongle; Wang, Shutong; Cao, Keqiang; Wang, Yanan (Frontiers in Microbiology, 2022)
Alternaria leaf blotch caused by Alternaria alternata apple pathotype (Alternaria mali) is an important fungal disease that affects the production of apples worldwide. Mycoviruses harbored in plant pathogenic fungi can confer hypovirulence in their hosts and have attracted widespread attention as potential biocontrol tools. In this study, the coinfection of two mycoviruses, named A. alternata chrysovirus 1 strain QY2 (AaCV1-QY2) and A. alternata magoulivirus 1 (AaMV1), respectively, were isolated from A. alternata f. sp. mali strain QY21. Sequence analyses revealed that AaCV1-QY2 virus belonged to the genus Betachrysovirus and AaMV1 virus belonged to the genus Magoulvirus. These two mycoviruses were found to be associated with hypovirulence in A. alternata, among which AaCV1-QY2 might play a relatively leading role. Because the elimination of AaMV1 from the strain QY21 does not affect the hypovirulence trait, which indicates that the virus AaCV1-QY2 can independently induce slow growth and reduce host virulence. Moreover, the presence of viruses decreased the accumulation of the mycotoxin alternariol (AOH) in A. alternata strains. Intriguingly, AaCV1-QY2/AaMV1 mycoviruses can be horizontally transmitted to other A. alternata strains, and this coinfection can promote the interspecific transmission efficiency of AaCV1-QY2. To our knowledge, this study reports the first description of the member of Chrysovirus is related to hypovirulence in Alternaria spp. that facilitates the development of biocontrol measures of A. mali Roberts.